Soybean Meal Alternatives in Rabbit Diets – A Review of Central European Research - Gugołek, Małgorzata; Krzykawski, Adrian; Czajkowska, Jagoda (Polish Journal of Natural Sciences, 2023)
Soybean meal (SBM) is a by-product of soybean processing, and it is widely used as a component of diets for various livestock species, including rabbits. However, at the beginning of the 21st century, researchers began to search for alternative high-protein feeds that could replace SBM in rabbit diets. The aim of the present study was to review, in chronological order, the literature on alternative feed ingredients as substitutes for SBM in rabbit diets in Central Europe in the 21st century. The authors reviewed studies investigating the replacement of SBM in rabbit diets with plant-based protein sources such as maize and wheat distillers’ dried grains with solubles (DDGS), rapeseed meal, rapeseed cake, white lupine seeds, peas, and silkworm pupae and mealworm larvae meals. The analysis revealed that SBM in rabbit diets can be completely or partially replaced with other high-protein plant ingredients and insect meals without compromising the performance of animals.